Peningkatan Kedisiplinan Prajurit melalui Pola Komunikasi Kepemimpinan Militer - Muhammad Akbar; Nahdiana Nahdiana (Journal of Communication Sciences (JCoS), 2023)
Discipline is basically a must for a TNI soldier. The establishment of soldier discipline has been carried out since the basic soldiering education period, then it is the responsibility of the leader of each soldier to always maintain soldier discipline, including for the planning division leader at the XIV/Hasanuddin Makodam, soldier discipline is the responsibility of an Asren. From the explanation above a number of questions arise, what are the patterns of leadership communication in an effort to improve Soldier discipline and what are the factors that influence Soldier discipline in the planning department of the XIV/Hasanuddin Military Command Headquarters. This study used a qualitative descriptive method which took two months to collect and process data through interviews in order to answer the questions. Based on the results of interviews with key informants and secondary informants regarding leadership communication patterns in an effort to improve soldier discipline and the driving and inhibiting factors of soldier discipline, the researcher can conclude that basically efforts to increase soldier discipline have been carried out by the planning division leader of the XIV/Hasanuddin Kodam by using communication patterns. wheels and Y communication patterns. With these two communication patterns, soldiers feel more confident and comfortable communicating with leaders, because with these patterns, a soldier feels valued. In addition, several factors driving and inhibiting the communication and discipline of soldiers at the XIV/Hasanuddin Makodam include the leader's trust in subordinates, honesty, listening skills, and the use of appropriate language. Meanwhile, several factors inhibiting communication and soldier discipline are differences in status and position, language differences, and cultural differences which make communication unable to run efficiently.